Човекът на 60-те – българо-хърватски паралели. Предварителни бележки - Няголова, Наталия (SlavVaria, 2022)
Man of the 1960's – Bulgarian-Croatian parallels. Preliminary notes. The article traces the functioning of similar artistic features in two literary texts of Bulgarian and Croatian culture from the 1960s. The appearance of these features is motivated by the influences both of the national modernist paradigm and Western art of the period. A number of distinctions have been made between the specifics of the defined features and the socialist realist canon of the Soviet Thaw.